The Interaction Of Organizational Culture, Leadership Style The Head Of School And Conflict Management On The Performance Of Secondary School Teachers - Haryaka, Usfandi (CV. Inara, 2021)
The purpose of this study was To determine the interaction of the influence of principal's leadership style on the performance of teachers of SMP Negeri Samarinda, to determine the interaction effect of organizational culture in learning on the performance of teachers of SMP Negeri Samarinda, and to determine the interaction of organizational conflict on the performance of teachers of SMP Negeri Samarinda. This research was conducted in the First high School Was with the research sample as many as 65 people teachers drawn randomly against six Secondary Schools in Samarinda. The research method used is the method of suvey with data collection techniques using a questionnaire followed by an interview with prewakilan teachers drawn randomly 5 teachers from each school. Data analysis used is path analysis (path analysis).The findings of the study show that:(1) organizational Culture has a direct effect on the Performance of Teachers amounted to 14.82% with path coefficient 0,385 (2) the principal's Leadership Style has a direct effect on the Performance of Teachers by 5.25% with a path coefficient 0,230, and (3) Conflict Management has a direct effect on the Performance of Teachers by 11,29% with path coefficient 0,336. Research conclusions:(1) organizational Culture has a direct impact significantly on the Performance of Teachers, (2) the principal's Leadership Style has a direct impact significantly on the Performance of Teachers, and (3) Conflict Management has a direct impact significantly on the Performance of Teachers.